2018
DOI: 10.1136/bjophthalmol-2018-312010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of intercapillary area with visual acuity in diabetes mellitus: an optical coherence tomography angiography study

Abstract: Increased ICA measured from OCT-A, describing enlargement of capillary rarefaction or closure at macular area, is independently associated with BCVA, suggesting that ICA is a potential marker to quantify retinal microvascular abnormalities relating to vision among individuals with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 28 publications
1
9
0
1
Order By: Relevance
“…However, pre-treatment mean ICA was significantly associated with baseline BCVA. Our results are similar to Tang et al, 28 who confirmed the relationship between ICA and BCVA and DR severity in their cross sectional study over 477 eyes.…”
Section: Discussionsupporting
confidence: 93%
“…However, pre-treatment mean ICA was significantly associated with baseline BCVA. Our results are similar to Tang et al, 28 who confirmed the relationship between ICA and BCVA and DR severity in their cross sectional study over 477 eyes.…”
Section: Discussionsupporting
confidence: 93%
“…Enlargement of FAZ due to capillary nonperfusion is associated with significant visual loss in patients with diabetic retinopathy [14][15][16], and has shown to be a prognostic indicator of disease severity [7,24,47]. Previous histopathological studies of diabetic retina have reported that the frequency of diabetic vascular lesions was significantly higher in the temporal retina than in the nasal retina [48,49].…”
Section: Within-subject Faz Area Enlargementsmentioning
confidence: 99%
“…A number of studies using intravenous fluorescein angiography (IVFA) or optical coherence tomography (OCT) angiography have utilized the detection of retinal vascular abnormalities and foveal avascular zone (FAZ) enlargement to assess the severity of diabetic retinopathy [5][6][7][8][9][10][11][12][13]. Altered configuration and enlargement of the FAZ has shown strong correlation with poorer visual outcomes and diabetic retinopathy progression [14][15][16], making quantification of FAZ dimensions increasingly important for assessment of clinical severity and predicting prognosis in diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Reconstruction of multiple macular B-scans by powerful computer processors can, therefore, provide us with noninvasive en-face OCT scans of retinal and choroidal layers of various depths, which can help in the understanding of various retinal conditions. 710…”
Section: Introductionmentioning
confidence: 99%